Pendampingan Percepatan Pengentasan Kemiskinan Melalui Budidaya Cacing Tanah (Lumbricus Rubellus) di Kecamatan Soko Kabupaten Tuban - Kresna Oktafianto; Raka Nur Sukma; Kuntum Febriyantiningrum; Dwi Oktafitria; Henny Murnafikhoh; Habib Al Mahdi; Rahmatullah Rahmatullah (Abdimas Universal, 2019)
One of the efforts to alleviate poverty in Soko Sub-District, Tuban Regency is giving an assisting program in the cultivation of earthworms (Lumbricus rubellus). This program is aimed for groups of farmers in Soko Sub-District, Tuban Regency. This Community Service Activity (PKM) was carried out by using a method in the form of training activities for earthworm cultivation (Lumbricus rubbelus) starting from the provision of materials, preparation of earthworm media, seed sowing, feed making, feeding, routine maintenance, harvesting techniques and monitoring of PKM implementation team. Mentoring and monitoring activities were observed with cultivation implementation observation instruments, observation sheets on worm cultivation, and participant response questionnaires. This community service ended with the submission of earthworm seedlings (Lumbricus rubbelus) to the participants of farmer groups in Soko Sub-district, Tuban Regency as the initial capital to start earthworm cultivation (Lumbricus rubbelus). The results of Community Service showed that the average responsiveness of earthworm cultivators in Soko Subdistrict showed very good (4.1%), good (34.8%), sufficient (39.8%)and the remaining was lacking and continuous technical guidance and assistance needed to get maximum results (21.3%).